Analysis of gut bacteriome of in utero arsenic-exposed mice using 16S rRNA-based metagenomic approach - Shukla, Shagun; Srivastava, Ankita; Verma, Digvijay; Gangopadhyay, Siddhartha; Chauhan, Anchal; Srivastava, Vikas; Budhwar, Savita; Tyagi, Dushyant; Sharma, Deepak Chand (Frontiers in Microbiology, 2023)
Approximately 200 million people worldwide are affected by arsenic toxicity emanating from the consumption of drinking water containing inorganic arsenic above the prescribed maximum contaminant level (MCL). The current investigation deals with the role of prenatal arsenic exposure in modulating the gut microbial community and functional pathways of the host. For this, 16S rRNA-based next-generation sequencing was carried out to understand the effect of in-utero 0.04 mg/kg (LD) and 0.4 mg/kg (HD) of arsenic exposure was carried out from gestational day 15 (GD-15) till the birth of pups to understand the alterations in bacterial diversity. The study focused on gestational exposure to arsenic and the altered gut microbial community at phyla and genera levels along with diversity indices. A significant decrease in the Firmicutes was observed in the gut microbiome of mice treated with arsenic. Functional analysis revealed that a shift in genes involved in crucial pathways like insulin signaling and non-alcoholic fatty liver disease pathways may lead to metabolic diseases in the host. The present investigation may hypothesize that in-utero arsenic exposure can perturb the gut bacterial composition significantly as well as the functional pathways of the gestationally treated pups. This research paves the way to further investigate the probable mechanistic insights in the field of maternal exposure environments which may play a key role in epigenetic modulations in developing various disease endpoints in the progeny.